Financial strain and depression in the U.S.: a scoping review - Catherine K. Ettman; Alice Y. Fan; Alexander P. Philips; Gaelen P. Adam; Grace Ringlein; Melissa A. Clark; Ira B. Wilson; Patrick M. Vivier; Sandro Galea (Translational Psychiatry, 2023)
Abstract While the association between assets and depression has been established, less is known about the link between financial strain and depression. Given rising financial strain and economic inequity due to the COVID-19 pandemic, understanding the role that financial strain plays in shaping population depression in the United States is particularly salient. We conducted a scoping review of the peer-reviewed literature on financial strain and depression published from inception through January 19, 2023, in Embase, Medline via PubMed, and PsycINFO, PsycArticles, SocINDEX, and EconLit via Ebsco. We searched, reviewed, and synthesized the literature on longitudinal studies on financial strain and depression conducted in the United States. Four thousand and four unique citations were screened for eligibility. Fifty-eight longitudinal, quantitative articles on adults in the United States were included in the review. Eighty-three percent of articles (n = 48) reported a significant, positive association between financial strain and depression. Eight articles reported mixed results, featuring non-significant associations for some sub-groups and significant associations for others, one article was unclear, and one article reported no significant association between financial strain and depression. Five articles featured interventions to reduce depressive symptoms. Effective interventions included coping mechanisms to improve one’s financial situation (e.g., mechanisms to assist in finding employment), to modify cognitive behavior (e.g., reframing mindset), and to engage support (e.g., engaging social and community support). Successful interventions were tailored to participants, were group-based (e.g., they included family members or other job seekers), and occurred over multiple sessions. While depression was defined consistently, financial strain was defined variably. Gaps in the literature included studies featuring Asian populations in the United States and interventions to reduce financial strain. There is a consistent, positive association between financial strain and depression in the United States. More research is needed to identify and test interventions that mitigate the ill effects of financial strain on population’s mental health.